A randomised, double-blind, placebo-controlled, multicentre clinical trial of AZD1656 in diabetic patients hospitalised with COVID-19: The ARCADIA Trial - implications for therapeutic immune modulation. (September 2022) - Chorlton, Jamie; Hollowood, Zoe; Dyer, Carlene; Lockhart, Donna; Boekman, Pascal; McCafferty, Kieran; Coffey, Pete; Marelli-Berg, Federica; Martin, John
Summary: Background: A potential immunotherapeutic role for AZD1656 (a glucokinase activator) in the treatment of COVID-19 was hypothesized. The ARCADIA trial investigated the safety and efficacy of AZD1656 in diabetic patients admitted to hospital with COVID-19. Methods: The ARCADIA trial was a Phase II randomised, double-blind, placebo-controlled clinical trial. Adult diabetic patients, admitted with COVID-19, were recruited at 28 hospitals in the UK, Romania and Czech Republic and randomly assigned (1:1) to receive AZD1656 tablets (100mg twice a day), or matched placebo, for up to 21 days, in addition to usual care. All involved were masked to treatment allocation. The primary endpoint was clinical improvement measured at Day 14. The Full Analysis Set (FAS) included all patients who received at least one dose of assigned treatment. ARCADIA is complete and registered with ClinicalTrials.gov (NCT04516759 ). Findings: Between 29 September 2020 to 16 April 2021, 170 patients were screened and 156 patients were randomised, three of whom did not commence treatment. Of the remaining 153, 80 were assigned to AZD1656 and 73 were assigned to placebo and included in the Full Analysis Set (FAS). The primary analysis showed no statistically significant difference between groups (AZD1656: 76·3%; Placebo: 69·9%, p= 0·19). There was no difference in the number of adverse events between groups (AZD1656: 35·7%; Placebo: 33·3%). Mortality was lower in the AZD1656 group compared to the placebo group (AZD1656: four (5%); Placebo: nine (12·3%), p= 0·090)). At Day 7 there were zero deaths in the AZD1656 group compared to six deaths in the placebo group ( p= 0·011, post hoc). A difference between groups in time to hospital discharge was also seen ( p= 0·16). Immunophenotyping data suggested that AZD1656-treated patients had a less pro-inflammatory immune response and a better adaptive immune response than those treated with placebo. Interpretation: Although the trial did not achieve its primary endpoint, AZD1656 was associated with a decrease in deaths and a reduction in the duration of hospitalisation, as compared to Placebo. Immunophenotyping and immunochemistry indicated an immunomodulatory effect of AZD1656. The trial suggests a beneficial therapeutic effect of AZD1656 and identifies a new therapeutic concept: small molecule activation of endogenous homeostatic immune cells which themselves become the therapeutic agent within the body. Phase 2 trials of this size carry the risk of false positive results and confirmation of these results in a larger clinical trial is now required. Funding: UK Research and Innovation (UKRI) 'Innovate UK' programme and Excalibur Medicines Ltd.